Dental prevention habits in adults attending special-care schools. A questionnaire study of parents/caregivers - Gerreth, Karolina; Gerreth, Piotr (Polish Journal of Public Health, 2011)
Introduction. Patients with disabilities and certain systemic diseases often have difficulties in maintaining oral hygiene at an appropriate level due to reduced manual dexterity, lack of understanding of the need of regular tooth brushing as well as that of support of parents/ caregivers in carrying out this procedure. Moreover, dietary habits in this population are not satisfactory. Aim. The study aimed at evaluating dental prevention habits in adult students from special-care schools in Poznan on the basis of a questionnaire study of their parents/caregivers. Material and methods. The study covered 65 people, parents or caregivers of intellectually disabled students, aged 19-24 years, attending special-care schools in Poznan. The closed questions concerned tooth brushing frequency, self-dependence in teeth cleaning, the kind of toothbrush, the use of mouthrinse, chewing gum as well as dental floss and the need to keep a special diet, the preferred texture of foods, snacking between meals and after evening tooth brushing. Results. A high percentage of parents/caregivers (81.6%) declared that their children clean the teeth more than once daily and 66.2% of the children were self-dependent in this respect. Most of the children (73.8%) used only the traditional manual toothbrush. Mouthrinse was used only by 13.8%, chewing gum by 40.0%, while dental floss by 6.2% of disabled students. Most children snacked between meals (70.7%) and after the evening tooth brushing (36.9%). Only 6.2% of students used a special diet, 35.4% preferred soft food, whereas 4.6% preferred solid food. Conclusions. The study revealed a need for improvement of hygienic and dietary habits in adult special-care students. It would be advisable to set up educational programs for the prevention of oral diseases targeted at their parents/caregivers, teachers as well as health professionals in special-care schools.